Dialectics and the Relationship between Philosophy and Religion in an Islamic Perspective - Muhammad Adip Fanani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
. Islamic philosophy and religion have undergone long phases of ups and downs, becoming a dialectic of science. Religion and philosophy in the academic world view are two entities that cannot be separated when studied academically to find the truth. Ibn Rushd asserted that the religion of sharia and the philosophy of wisdom do not conflict. Indeed, there was tension between theologians, especially al-Ghazâlî in Tahâfut al-Falasifah, and Islamic philosophers, especially peripatetic philosophers, such as Ibn Sina. This tension is reflected in Ibn Rushd's statement that